RETRACTED ARTICLE: Phyto-assisted synthesis of zinc oxide nanoparticles using Bauhinia variegata buds extract and evaluation of their multi-faceted biological potentials - Sehrish Arafat; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Tabassum Yaseen; Ghulam Murtaza; Rafi Ullah; Farishta Zarshan; Zakir Ullah; Zulfiqar Ali Sahito; Saeedah Musaed Almutairi; Mohamed S. Elshikh; et al. (Scientific Reports)
Abstract Zinc oxide nanoparticles have wide range biological, biomedical and environmental applications. However, traditional nanofabrication of ZnONPs uses various toxic chemicals and organic solvents which limit their bio-applications. To overcome this hurdle, Bauhinia variegata derived buds extract was utilized to fabricate ZnONPs. The greenly generated ZnONPs were successfully prepared and extensively characterized using different analytical tools and the average crystalline size was calculated as 25.47 nm. Further, bioengineered ZnONPs were explored for multiple biological activities that revealed excellent therapeutic potentials. The antibacterial potential was determined using different bacterial strains. Pseudomonas aeruginosa (MIC: 137.5 µg/mL) was reported to be the most resistant variant while Bacillus subtilis (MIC: 34.38 µg/mL) was observed to be most susceptible bacterial strain. DPPH radical scavenging potential was measured to determine the antioxidant capacity of ZnONPs and the highest scavenging potential was observed as 82% at highest of 300 µg/mL. The fungicidal effect of green ZnONPs in comparison with Amphotericin B was assessed against five selected pathogenic fungal strains. The results revealed, Fusarium solani (MIC: 46.875 µg/mL) was least resistant and Aspergillus flavus (MIC: 187.5 µg/mL) was most resistant in fungicidal examination. Cytotoxicity potential of B.V@ZnONPs was analyzed against newly hatched nauplii of brine shrimps. The results for greenly produced ZnONPs was recorded as 39.78 µg/mL while 3.006 µg/mL was reported for positive control vincristine sulphate. The results confirmed the category of general cytotoxic for greenly synthesized nano sized B.V@ZnONPs.